Multi-Objective Optimization Design of Ladle Refractory Lining Based on Genetic Algorithm - Sun, Ying; Huang, Peng; Cao, Yongcheng; Jiang, Guozhang; Yuan, Zhongping; Bai, Dongxu; Liu, Xin (Frontiers in Bioengineering and Biotechnology, 2022)
Genetic algorithm is widely used in multi-objective mechanical structure optimization. In this paper, a genetic algorithm-based optimization method for ladle refractory lining structure is proposed. First, the parametric finite element model of the new ladle refractory lining is established by using ANSYS Workbench software. The refractory lining is mainly composed of insulating layer, permanent layer and working layer. Secondly, a mathematical model for multi-objective optimization is established to reveal the functional relationship between the maximum equivalent force on the ladle lining, the maximum temperature on the ladle shell, the total mass of the ladle and the structural parameters of the ladle refractory lining. Genetic algorithm translates the optimization process of ladle refractory lining into natural evolution and selection. The optimization results show that the insulating layer thickness is 8.17mm, the permanent layer thickness is 76.15mm, and the working layer thickness is 152.19mm. The refractory lining has the best thermal insulation performance. Finally, the simulation analysis of the results obtained after optimization is carried out in this paper. The study found that by optimizing the design of the ladle refractory lining, the maximum equivalent force on the ladle lining, the maximum temperature on the ladle shell and the ladle mass were reduced. The thermal insulation performance and the lightweight performance of the ladle are improved, which is very important for improving the service life of the ladle.